Better understanding of exchange rate effects in destination marketing: Cases of the Czech Republic and Croatia - Vojtko, Viktor; Štumpf, Petr; Kovačič, Mirjana; Janeček, Petr (Institute for Tourism, 2018)
Exchange rates can be considered as one of the important determinants in tourism demand analysis especially at the national level, although sensitivity of demand to exchange rate changes may also vary by destination. The main goal of this paper is to compare the impact of changes in nominal exchange rates on the number of visitors from Eurozone countries in two specific destinations: Croatia, representing Southern Europe/Mediterranean predominantly ‘sun and sea’ destination and the Czech Republic, as a Central and Eastern European country and a typical cultural destination. A generalized linear model was used for data analysis and hypothesis testing. This paper identifies relationship between seasonally cleaned changes in the number of incoming tourists from Eurozone and average changes in monthly nominal exchange rate lagged between one and twelve months. The results show that there are significant differences in sensitivity of international tourism demand from Eurozone to changes in exchange rate between Czech Republic and Croatia and that delays in reaction to such changes are as expected different as well. The findings could improve short term forecasting of tourism demand as well as marketing targeting of destination management organization activities. The results of this study can be practically used by National Tourism Organizations (NTOs) for marketing activities, because it is possible to reveal the tourists’ behaviour from the source markets point of view. These findings, based on secondary data, could be used as a support tool for destination marketing, partially instead of primary data collection within the source markets.
Lepší porozumění efektu směnných kurzů v destinačním marketingu: Případy České republiky a Chorvatska
Keywords: Croatia; Czech Republic; Destination Marketing; Exchange Rate; Exchange Rate Changes; Tourism Demand; Chorvatsko; Česká republika; destinační marketing; směnný kurz; změna směnných kurzů; poptávka turismu